Epistemology in Islamic Philosophy: The Integration of Reason, Revelation, and Intuition as a Spiritual Path - Yosie Kristin Pandriyani; Hodiqotul Atfaliyah; Wasehudin Wasehudin; Erdi Rudjikarwati; Agus Gunawan (International Journal of Islamic Studies Higher Education, 2025)
This study aims to examine epistemology within the tradition of Islamic philosophy and its relevance as a spiritual path for humanity toward God. Islamic philosophy views knowledge not merely as a rational activity, but as a process of spiritual transformation that integrates reason, revelation, and intuition (ma‘rifat). This study employs a qualitative method using a content analysis design. Data sources consist of classical Islamic philosophical texts and relevant literature, with the units of analysis being the concepts of epistemology and spirituality. Data were collected through a literature review and analyzed thematically using the Miles and Huberman model with the assistance of NVivo software. The findings indicate that the epistemology of Islamic philosophy has a teleological orientation, wherein the ultimate goal of knowledge is the attainment of divine consciousness and the perfection of human existence. The integration of rational and spiritual dimensions in Islamic epistemology positions knowledge as a means of purifying the soul and drawing closer to God. This study affirms that epistemology in Islamic philosophy is not merely a theoretical framework but also the foundation of the human spiritual path. These findings offer a conceptual contribution by proposing a holistic and relevant epistemological paradigm to address the crisis of meaning and spirituality in modern humanity.